HYDROTHERMAL CO-LIQUEFACTION OF PROSOPIS JULIFLORA AND POLYPROPYLENE IN CONTINUOUS HIGH PRESSURE SCREW REACTOR: A COMPUTATIONAL AND EXPERIMENTAL ANALYSIS - VENKATACHALAM, Chitra Devi; BHUVANESHWARAN, Premkumar; SENGOTTIAN, Mothil; RAVICHANDRAN, Sathish Raam (Studia Universitatis Babeș-Bolyai Chemia, 2025)
In advancement over batch reactors for biomass conversion, a continuous high-pressure screw reactor was designed to perform hydrothermal co-liquefaction (co-HTL) under a range of conditions: temperatures of 555–595 K, water-to-biomass ratios (W/B) of 6.3–8.3, and feed rates of 0.005–0.0085 kg/s. Prosopis juliflora (PJ) and polypropylene (PP) were used in biomass ratios of 1:4, 1:1, and 4:1. Computational Fluid Dynamics (CFD) using ANSYS Fluent was employed to analyze heat transfer between the reaction chamber and slurry biomass. For 595 K, 8:3 W/B, and 0.007 kg/s, the simulation predicted a maximum temperature of 589.3 K and pressure of 22.1 MPa, showing a 1.3 MPa deviation from experiments due to low-density particles and higher process temperatures. The simulated heat transfer coefficient was 6001 W/m2K, matching experimental data with 94.6% accuracy. Under these conditions, energy recovery reached 70.8%, with biochar and biocrude yields of 34.2% and 48.7%, respectively. A synergistic effect in biocrude and biochar production was observed at a 4:1 PJ:PP ratio, independent of temperature. GC-MS analysis confirmed major aromatic hydrocarbons, including 1-[(E)-2-(4-chlorophenyl)ethenyl]-3,5-dimethoxybenzene, 2-methoxyphenol (C7H8O2), and phenol (C6H5OH). The optimal conditions of 595 K, 8:3 W/B, and 0.007 kg/s are recommended for maximum energy recovery and efficient heat transfer.